2021
DOI: 10.12750/jarb.36.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Isoprocarb induces acute toxicity in developing zebrafish embryos through vascular malformation

Abstract: In this study, the potential toxicity of isoprocarb was demonstrated using zebrafish embryos. We treated isoprocarb (0, 29, and 58 mg/L) to the zebrafish embryos for 72 h then, we estimated morphological changes and apoptotic cell numbers. The increasing extent of apoptosis from the anterior to posterior region of developing zebrafish larvae was correlated with toxicity in the overall development process, including growth and normal organ formation. The appearance of abnormalities in the isoprocarb-treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Interestingly, 200 μM PA significantly increased tiRNA expression in trophoblasts. Differences in the expression of tiRNAs depending on the concentration of PA require further study; however, a recent study on angiogenin-mediated inflammation-induced metabolic disease suggests a new link between tiRNA generation and inflammation (Park et al, 2021;Zhang et al, 2021). Angiogenin expression is increased in the mouse caput epididymis by LPS, and inflammation is inhibited in mice lacking angiogenin, accompanied by a change in the tRNA-derived species profile.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 200 μM PA significantly increased tiRNA expression in trophoblasts. Differences in the expression of tiRNAs depending on the concentration of PA require further study; however, a recent study on angiogenin-mediated inflammation-induced metabolic disease suggests a new link between tiRNA generation and inflammation (Park et al, 2021;Zhang et al, 2021). Angiogenin expression is increased in the mouse caput epididymis by LPS, and inflammation is inhibited in mice lacking angiogenin, accompanied by a change in the tRNA-derived species profile.…”
Section: Discussionmentioning
confidence: 99%
“…Adult wild-type (AB strain) and transgenic (flk1:eGFP) zebrafish lines acquired from the Zebrafish Organogenesis Mutant Bank (Kyungpook National University, Korea) were maintained as previously reported (Park et al, 2021).…”
Section: Experimental Organismmentioning
confidence: 99%
“…Despite the extensive use of picolinafen, its molecular mechanisms in non-target cells have not been extensively studied. Previous studies have shown high bioaccumulation and reproductive toxicity of herbicides in sh (An et al 2021;Park et al 2021;Yang et al 2021). In addition, research on the toxic effects of herbicides in murine preimplantation embryos revealed that exposure to low-dose herbicides increased apoptosis and inhibited blastocyst development (Greenlee et al 2004).…”
Section: Introductionmentioning
confidence: 98%